Cage Metal Complexes: Synthesis, X‐ray Structure, and Spectral and Redox Behavior of the First Hybrid Iron(II) Clathrochelatoscorpionate and Its Pyrazoloxime‐Armed Macrocyclic Intermediate. Issue 12 (7th February 2013) - Varzatskii, Oleg A.; Kats (Menkach), Svitlana V.; Penkova, Larysa V.; Volkov, Sergey V.; Dolganov, Alexander V.; Vologzhanina, Anna V.; Bubnov, Yurii N.; Voloshin, Yan Z.
Abstract: Cycloaddition of a new pyrazoloxime to macrocyclic iron(II) bis(α‐benzyldioximate) unexpectedly gave a mixture of the first hybrid clathrochelatoscorpionate and its pyrazoloxime‐armed macrocyclic intermediate, which were characterized by X‐ray crystallography, spectroscopy, and cyclic voltammetry. Abstract : The first hybrid clathrochelatoscorpionate and its pyrazoloxime‐armed macrocyclic intermediate were obtained by cycloaddition of a new pyrazoloxime to macrocyclic iron(II) bis(α‐benzyldioximate) and characterized by X‐ray crystallography, spectroscopy, and cyclic voltammetry.